Sistem Pendukung Keputusan Pemilihan Calon Kepala Desa menggunakan metode Fuzzy Simple Additive Weighting (F-SAW) (Studi Kasus Pada Desa Noelbaki Kecamatan Kupang Tengah Kabupaten Kupang) - Kornelis Letelay; Sarah Nuban; Metion Boru (Universitas Nusa Cendana, 2020)
In the election of candidates of the village head must be through an assessment whether the candidates of the village head is feasible or unfit. BPD Noelbaki has set the assessment standards in the election of the village head of the village since the beginning of the election to date. The election is done based on the criteria that have been established, among others, education, domicile, personality, legal status, political parties, work, income and age. In the study was done design and manufacture of application decision support system with fuzzy simple additive weighting (F-SAW). This method is able to accommodate the shortcomings of saw methods in linguistic and numerical assessments. Testing system is done by comparing the result of the system and the results of the expert. From the results of the system validation testing provided by the BPD against 30 alternative data, obtained value 90% accuracy with error rate of amount 10% which shows that the decision support system work with optimally according to the method of F-SAW.The results of this research is the application system of decision support of the election of candidate village by the district of several alternatives (candidate of the village head), which can be a BPD recommendation for decision making. Afer testing of the 30 test data, with input value of the same interest for each criterion, so obtained presentation of the strict constitution competition and BPD bank state decision by 90%, where there are 3 resuluts of the districts that are rejected with the assessment standards of the BPD.